A Cross-Cultural Investigation of the Five-Factor Narcissism Inventory Short Form: Narcissism as a Multidimensional Trait in the United Kingdom and Russia. Issue 3 (4th May 2022) - Papageorgiou, Kostas A.; Denovan, Andrew; Dagnall, Neil; Artamonova, Elena
Abstract: Research on narcissism supports a multifactorial structure with each factor to be multidimensional. However, studies typically assess 1 factor of narcissism using scales such as the Short Dark Triad (SD3). The Five-Factor Narcissism Inventory and its short form (FFNI–SF) were developed recently to account for this issue. The extent to which the FFNI–SF assesses equivalent constructs across countries has, nonetheless, received little attention. This study evaluated the factor structure of the FFNI–SF in a Russian sample ( N = 1, 996) and compared the results with those derived from a UK sample ( N = 1, 292). Overall, the FFNI–SF evidenced satisfactory internal consistency (mean α = .82 and .79 for the Russian and UK sample for the factors of Antagonism, Extraversion and Neuroticism, respectively). Additionally, analyses yielded a 3-component model in both samples similar to that reported in the original validation study, which also demonstrated meaningful correlations with the SD3. Finally, Antagonism demonstrated significant differences between the 2 samples, perhaps reflecting societal differences between Russia and the United Kingdom. The study highlights the importance of using psychometrically sound measures to assess narcissism in its complexity and the need for additional research on how this trait operates within the personality sphere and across cultures.